DESCRIPTION OF THE EFFORTS OF PARENTS WITH DOWN SYNDROME CHILDREN ON DEVELOPMENT OF FIRST LANGUAGE ACQUISITION: - - Rahmi Khalida (JURNAL KESEHATAN MERCUSUAR, 2019)
Down's syndrome is one type of child with special needs. The existence will affect the quality of family life by influencing what happens to them. This study aims to describe the efforts of parents on the development of the first language acquisition of children with Down syndrome. The method used in this study is a qualitative method using descriptive qualitative. Research data were collected through interviews and observations. The subject of this study supports two families who have Down syndrome children. Data processed by content analysis. From the results of the study showed that the requirements for the ability to obtain child assistance from the stimulus from the beginning that represents acceptance in children by the microsystem environment that is family.